ANALISIS MASLAHAH TERHADAP HIBAH HARTA PADA ANAK DIBAWAH UMUR DARI PEMBAGIAN HARTA GONO-GINI - Salma Mazidah; Suprihatin Suprihatin; Baiduri Baiduri (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
This research was conducted because of the discovery of peace decision No.3792/Pdt.G/2018/PA.Bks. regarding the distribution of the property of gono-gini which is not only divided between husband and wife but also given to minors. Giving assets to minors originating from the distribution of joint assets can have similarities with grants because parents hand over some of their assets to transfer ownership to their children who are also domiciled as a living. The formulation of the problem in this study concerns the positive impact of giving assets to children who are not yet mature with the formula "What are the benefits of giving property grants to minors that are sourced from the distribution of assets gono-gini (study on the peace deed no 3792/Pdt.G/2018/ PA.Bks) ". The purpose of this study is to find out the maslahah or goodness of granting assets to minors originating from the distribution of assets gono-gini (study on the peace deed no.3792/Pdt.G/2018/PA.Bks.). The research method used is a normative juridical method with a maslahah approach and library research. The primary legal material for this research is the judge's decision No.3792/Pdt.G/2018/PA.Bks. concerning the Peace Deed. The secondary legal materials are books related to grants from the perspective of fiqh and Islamic law, the concept of benefit and dictionaries, etc. The results of this study are that the provision of grants to minors originating from joint property contains 4 benefits, namely as follows: 1). Legally, children have legal certainty regarding the right to property for a child for the provision of life; 2). Economically, children have a clear source of life due to the divorce of their parents; 3). Socially, children have economic power in life in society so they are not marginalized by their environment; 4). Normatively grants to minors sourced from joint assets in accordance with the value of maqasid syar'i hifdun-nasl